Analisa Drug Related Problems pada Pasien Hiperurisemia di Bangsal Rawat Inap dan Rawat Jalan Penyakit dalam RSUP Dr. M. Djamil Padang - Anjelin, Ririn; Arifin, Helmi; Raveinal, Raveinal; Darwin, Deswinar (Fakultas Farmasi Universitas Andalas, 2012)
This research was a prospective observational study using descriptive cross sectional approach and performed at all patients of hyperuricemia with or without accompanying diseases at Interne Ward and Polyclinic DR. M. Djamil Hospital Padang during Maret to May 2011, by census. The data obtained were analyzed using descriptive analysis method. Results showed that type of DRPs frequently occured at 110 patients with hyperuricemia with/without  accompanying diseases at Interne polyclinic was drug interactions of pharmacokinetic and pharmacodynamic at 36 patients. Adverse drug reaction 9 patients, non-compliance of patients 5 patients. Drug terapy without medical indication, lower and higher dose, inappropriate drug selection, inappropriate drug administration interval were had no problems. At the Interne Ward from 7 patients, the DRPs frequentlyy occured were drug interactions (3 patients), higher drug dose (2 patients), adverse drug reactions (2 patients), patient non-compliance (2 patients), inappropriate drug administration interval (1 patient), drug therapy without medical indication (1 patient), and other DRPs had no problems. There was non toxic drug interactions or adverse drug reactions was found during this study.